Facing Trouble: How the African Union Handles Coups and Conflict Today - Elamin, Mustafa Osman I. (Journal of Posthumanism, 2025)
This study explores the African Union's (AU) response to escalating security challenges, including military coups and regional instabilities, through a posthumanist lens that interrogates the interplay of technology, humanity, and governance within the African Peace and Security Architecture (APSA). By examining APSA’s frameworks, the research highlights how emerging technologies, such as artificial intelligence (AI) and hybrid threat systems, reshape conflict dynamics and demand new ethical governance models. A mixed-methods approach integrates qualitative analysis of AU documents and secondary data from technologists with quantitative assessment of peace operation metrics, such as deployment efficiency and technological integration. . Key findings reveal systemic gaps in APSA, including funding shortages, delayed decision-making, and overreliance on external technological support, compounded by uneven regional capacities among Regional Economic Communities (RECs). The posthumanist perspective underscores the need to reframe African solutions by balancing technological advancements with human-centered ethical considerations, ensuring AI and digital systems enhance rather than destabilize security. The study advocates for adaptive governance frameworks that integrate RECs and prioritize local innovation to address hybrid threats. Implications point to a redefined technology-society nexus, where ethical AI deployment and regional collaboration strengthen APSA’s resilience. This research contributes to posthumanist discourse by situating African security within global debates on technology’s role in shaping future governance and stability.